Permanents: in defence of the moving spotlight theory - Deasy, DL (2014)
This thesis describes and defends the moving spotlight theory, a metaphysical theory concerning the fundamental temporal structure of reality. The moving spotlight theory has two essential components: first, a thesis about presentness; and second, a thesis about the existence (in the most general sense) of things over time. The first thesis is that exactly one instant of time is absolutely, objectively, non-relatively present. This thesis is usually called the ‘A-theory of time’. (The opposing view, according to which no instant of time is absolutely, objectively, non-relatively present, is usually called the ‘B-theory of time’.) The second thesis is that things neither begin nor cease to exist over time; in other words, that it is always the case that everything exists forever. Following Williamson (2013), I call this thesis permanentism. Historically, the moving spotlight theory has been among the least popular plausible theories of time. However, that is because the view has been badly misconstrued. In this thesis I provide a careful description of the moving spotlight theory and show that moving spotlighters can easily respond to the main arguments that have been raised against their view. I also show that the moving spotlight theory, when correctly understood, is the very best theory of time. In particular, the moving spotlight theory inherits the simplicity, explanatory power, and scientific respectability of permanentism, while at the same time describing a world in which there is genuine time and change. In terms of structure, the thesis has two parts, each containing three chapters. In Chapter One, I introduce the A-theory and defend it against some common objections. In Chapter Two, I describe a version of the moving spotlight theory which I call ‘classic MST’, and argue that if the moving spotlight theory is true, classic MST is true. In Chapter Three, I argue against the traditional method of characterising theories of time, and develop a new method in its place. In Chapter Four, I argue that the A-theory is true. In Chapters Five and Six, I argue that we think and speak as if permanentism is true, so we should accept permanentism. I conclude that the moving spotlight theory, and therefore classic MST, is true.